2023
DOI: 10.3389/fpubh.2023.1161234
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of the knowledge and attitude of Nepalese healthcare workers toward human monkeypox: a cross-sectional study

Santa Kumar Das,
Abhinav Bhattarai,
Simran KC
et al.

Abstract: Human monkeypox is an infectious zoonotic disease and since May 2022, there has been a spike in cases worldwide. In this regard, a global health emergency has been declared by the World Health Organization (WHO) on July 23rd, 2022. Although there have been no confirmed human monkeypox cases in Nepal yet, the nation is undeniably at risk of an outbreak. Despite all preventive efforts and preparedness for monkeypox, there still remain several challenges including the literacy and knowledge of our healthcare work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Furthermore, 43 literature reviews and 82 editorials were excluded, as they were not suitable for inclusion in this speci c review. As a result of the rigorous study selection process, 10 papers [15][16][17][18][19][20][21][22][23][24] were deemed eligible and included in the review. It is noteworthy that no additional reports of newly included studies were found.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, 43 literature reviews and 82 editorials were excluded, as they were not suitable for inclusion in this speci c review. As a result of the rigorous study selection process, 10 papers [15][16][17][18][19][20][21][22][23][24] were deemed eligible and included in the review. It is noteworthy that no additional reports of newly included studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the demographic factors relevant to the research on the assessment of HCWs KAP regarding Mpox is shown in Table 2. The studies [15][16][17][18][19][20][21][22][23][24] used cross-sectional study designs to gather data and were carried out in various nations. The studies' samples, which ranged from 163 to 639 HCWs, were different in size.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations